Assessment of knowledge management practice for curriculum development in case of Ethiopian Defence University - Dagne, A. K.; Lumadi, M. W. (South African Journal of Higher Education, 2024)
Knowledge represents the awareness and understanding of concepts, principles, procedures, or the relationships between various elements within a particular field or discipline. Organizations that recognize knowledge as a strategic asset can leverage it for resilience, problem-solving, decision-making, and innovation. Higher education institutions, as hubs of knowledge, play a crucial role in knowledge creation, organization, and dissemination. Effective knowledge management within these institutions enhances teaching, learning, research collaboration, and innovation. This research focuses specifically on the Ethiopian Defence University, a government higher education institution in Ethiopia. The study aims to assess the current level of knowledge management practices within the university, with a particular focus on its implementation for curriculum development. The research employs a quantitative research method with a descriptive survey design. The findings reveal a mixed state of awareness among academic staff members regarding the knowledge management system in higher education institutions. While some respondents demonstrated moderate familiarity with the system, the majority reported a lack of formal training. This highlights the need for increased attention to knowledge management practices within the university. The study also identifies deficiencies in the university’s knowledge management policies, strategies, and infrastructure. These include the absence of a centralized repository and a dedicated responsible body. Furthermore, knowledge-sharing activities and collaboration among faculty members were found to be poor, with limited incentives or recognition mechanisms in place. The implementation of a knowledge management system for curriculum development is also lacking, as evidenced by the absence of platforms for sharing knowledge and experience, a dedicated database system, and a centralized repository for curriculum materials.